A Scalable LDPC Coding Scheme for Adaptive HARQ Techniques - Madeira, João (2022)
This work was supported by the FCT - MASSIVE5G (SAICT-45-2017-02), as well as DAIS, which received funding from the Electronic Component Systems for European Leadership Joint Undertaking (ECSEL-JU) under Grant agreement number 101007273.